2017
DOI: 10.1021/acschembio.7b00458
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Interrogation of LuxR-type Quorum Sensing Receptors Reveals New Insights into Receptor Selectivity and the Potential for Interspecies Bacterial Signaling

Abstract: Cell-cell signaling between bacteria, including quorum-sensing (QS) communication systems, may play a role in the establishment and maintenance of polymicrobial communities. To better understand and model these interactions, we must uncover the degree to which neighboring species recognize each another’s signals. In the current study, we tested the likelihood of whether the QS systems of two opportunistic pathogens (Acinetobacter baumannii and Pseudomonas aeruginosa) that frequently arise in polymicrobial infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…We sought to examine a range of AHL-type scaffolds for activity in SdiA. We selected a series of sub-libraries from our in-house compound collections for analysis with demonstrated activities in other LuxR-type receptors, including TraR from Agrobacterium tumefaciens [ 45 , 51 54 ]; AbaR from Acinetobacter baumannii [ 47 , 55 ]; LasR [ 45 , 51 54 56 ], QscR [ 57 ], and RhlR [ 48 , 56 ] from Pseudomonas aeruginosa ; ExpR1 and ExpR2 from Pectobacterium carotovora [ 46 , 58 ]; and LuxR from Vibrio fischeri [ 45 , 51 54 ]. The full set of 151 compounds tested is shown in Supporting Information File 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We sought to examine a range of AHL-type scaffolds for activity in SdiA. We selected a series of sub-libraries from our in-house compound collections for analysis with demonstrated activities in other LuxR-type receptors, including TraR from Agrobacterium tumefaciens [ 45 , 51 54 ]; AbaR from Acinetobacter baumannii [ 47 , 55 ]; LasR [ 45 , 51 54 56 ], QscR [ 57 ], and RhlR [ 48 , 56 ] from Pseudomonas aeruginosa ; ExpR1 and ExpR2 from Pectobacterium carotovora [ 46 , 58 ]; and LuxR from Vibrio fischeri [ 45 , 51 54 ]. The full set of 151 compounds tested is shown in Supporting Information File 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Sub-libraries A and H contained AHLs with differing acyl tail lengths and oxidation levels at the tail β-carbon, including many naturally occurring AHLs [ 51 , 55 ]. The B and D sub-libraries were designed to test the effects of lactone stereochemistry, substitution of a variety of more structurally diverse and non-native functional groups on the acyl tail (e.g., alkyl, cycloalkyl, and aryl), and alkyl linker length between the head group and these functional groups [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Distinct from both of these cases, VqmA binds to either DPO or Ala-AA, but not both, to induce maximal transcriptional activity. This result is curious to us given that QS receptors typically maintain signaling fidelity by distinguishing between different ligands (30)(31)(32)(33). This situation appears analogous to that of the V. cholerae AI called CAI-1 ((S)-3hydroxytridecan-4-one) and its biosynthetic precursor, Ea-CAI-1 (3-aminotridec-2-en-4-one).…”
Section: Discussionmentioning
confidence: 99%
“…QS regulates biofilm formation, secondary metabolite production, and many other cellular processes. One of the most welldescribed QS systems is the homoserine lactone cluster, which is comprised of the signaling molecule synthase and the signal receptor (60,61). HSL clusters are identified in antiSMASH using hidden Markov models (HMMs) based on the Pfams for the synthetase (33).…”
Section: Resultsmentioning
confidence: 99%
“…HSL clusters are identified in antiSMASH using hidden Markov models (HMMs) based on the Pfams for the synthetase (33). While originally implicated in intraspecies communication, recent studies have also shown that QS molecules can be detected by nonproducing bacteria and even the host plant, whereby plant metabolism, the plant immune response, and root development can be modulated in response to the HSLs (16,60,62,63). Accordingly, the metagenomic analysis of the P. deltoides microbiome shows an enrichment of HSLs in the endosphere (Fig.…”
Section: Resultsmentioning
confidence: 99%